تقييم بيئة بركة ام النعاج ,هور الحويزه باستخدام دليل التكامل الحياتي - يونس, كاظم حسن (University of Thi-Qar Journal of Science, 2013)
The present work includes the study of the environment aspects of Um-ALnaaj, from January 2008-  Decenber2008. Twelve ecological metrices were chosen to calculate Integrated Biological Index (IBI) for the major ecological categories such as species richness, fish species composition and the diet composition.The average of (IBI) value of different months were 57.6 with the maximum value (73.0) during February and lowest value (31.0) during December. The statistical test showed there was a significant difference for IBI values (0.05) within different months.